LEGAL PROTECTION FOR CHILDREN UNDER 14 (FOURTEEN) YEARS OLD AGAINST VIOLENCE OFFENDER (ANALYSIS OF GARUT DISTRICT COURT DECISION NUMBER 1/PID.SUS-ANAK/2024/PN GRT) - Regina Monica Andriani; Harun Al Rasyid; I Nyoman Nurjaya (CV. RADJA PUBLIKA, 2025)
Garut District Court issued decision number 1/Pid.Sus-Anak/2024/PN Grt involving Akbar Rozak Alias Akbar who committed violence against the victim Agum Gumelar (deceased) until he died because he was annoyed by the victim who hit him hard while playing volleyball. The crime was committed by slashing 1 (one) cutter knife blade towards the victim's neck and right wrist and the victim was carried away by the Cimanuk River current. For his actions, the Panel of Judges imposed a correctional sanction for 1 (one) year at the Griya Bina Karsa Social Service Center-West Java Provincial Social Service in Cileungsi and participated in job training for 2 (two) months. This study aims to analyze the legal considerations (ratio decidendi) that have been used by the Panel of Judges in the decision of case number 1/Pid.Sus-Anak/2024/PN Grt and analyze the value of legal certainty and benefits for child perpetrators regarding the application of the law carried out by the Panel of Judges in the decision of case number 1/Pid.Sus-Anak/2024/PN Grt. The method used is normative juridical research with a case approach. The results of the study show that the Judge's considerations in decision number 1/Pid.Sus-Anak/2024/PN Grt which imposed sanctions on children were based on the principles of criminal law for children which are different from those for adults. The main focus is the best interest of the child, rehabilitation, and social reintegration. Several important elements in the legal considerations by the Judge consist of consideration of the principles of child protection, the age and maturity factors of the child, the severity of the violent crime committed, the child's attitude in court, recommendations from the Correctional Center, consideration of the type of sanctions, and the implementation of restorative justice. In decision number 1/Pid.Sus-Anak/2024/PN Grt in which the Panel of Judges imposed sanctions against the child, in fact the Panel of Judges did not explain the reasons for imposing other sanctions in the form of 2 months of job training. In fact, Akbar Rozak's child can only be subject to sanctions because he is not yet 14 years old. In addition, job training is one of the main types of punishment for children. So by simultaneously imposing sanctions in the form of action and criminal action against Akbar Rozak's child, it creates legal uncertainty, but on the other hand, imposing these sanctions can provide legal benefits for the child who committed the crime.